Georgia : Technical Assistance Report-Scanner Data for CPI. (IMF Staff Country Reports; Country Report ;, 2021)
The purpose of the mission was to assist the National Statistics Office of Georgia (Geostat) with continuing its modernization of the Consumer Price Index (CPI). This was the first technical assistance (TA) mission to Georgia to specifically focus on scanner data (SD). Two earlier missions on the residential property price index (RPPI) (September 23-October 4, 2019, and November 30-December 4, 2020) already provided initial guidance and addressed the planned modernization of the CPI using SD. The mission was delivered remotely, and the sessions were recorded for future reference.